2021
DOI: 10.3389/fped.2021.640236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Educational Video on Pre-operative Anxiety in Children - A Randomized Controlled Trial

Abstract: Objective: Audio-visual interventions have been used to provide relevant patient information to reduce pre-operative anxiety in children. The aim of the study was to investigate whether self-reported state anxiety in children could be reduced by presenting a child-friendly educational video on the day of surgery.Methods: A prospective, single-blinded, two-armed, randomized controlled study was designed with three measurement time points including 90 children (6–17 years) and their parents. In the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
6
0
2
Order By: Relevance
“…On the contrary, Uyar et al 12 failed to demonstrate the successful use of passive information based cartoon video in reducing preoperative anxiety in children between 5 and 8 years. Similarly, Harter et al did not find significant difference in anxiety levels in children watching educational video and those receiving standard information preoperatively 14 . Our study found noninferiority of information‐based video technique to self‐selected video technique in decreasing preoperative anxiety.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…On the contrary, Uyar et al 12 failed to demonstrate the successful use of passive information based cartoon video in reducing preoperative anxiety in children between 5 and 8 years. Similarly, Harter et al did not find significant difference in anxiety levels in children watching educational video and those receiving standard information preoperatively 14 . Our study found noninferiority of information‐based video technique to self‐selected video technique in decreasing preoperative anxiety.…”
Section: Discussionsupporting
confidence: 59%
“…[8][9][10][11] However, the literature about the use of video-based preoperative information technique for anxiety reduction in children still remains understudied with conflicting results. [12][13][14] Age appropriateness forms the basis of any nonpharmacological intervention for anxiety reduction in children. School going children begin to think logically and start applying reasoning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that educational videos lead to improvements in hemoglobin A 1c levels in patients with diabetes mellitus [ 32 ], improved satisfaction and comfort in patients undergoing transradial coronary angiography [ 33 ], and improved medication compliance in a population with rheumatoid arthritis [ 34 ]. However, videos were not successful in improving preoperative anxiety in a pediatric population [ 35 ]. Although short videos might change short-term beliefs and satisfaction with care, a more extensive intervention is likely needed to change behavior.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce children's preoperative anxiety and improve children's cooperation during the induction of anesthesia, pediatric staff have implemented a variety of distraction strategies. In hospitals, several distraction techniques are used to reduce children's anxiety prior to anesthesia induction; these techniques can also be used during parental separation (Härter et al, 2021;Sjöberg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%